Long-Term Impact of Recurrent Acute Otitis Media on Balance and Vestibular Function in Children - Mirko Aldè; Pietro Bosi; Stefanie Muck; Thomas Mayr; Paola Di Mauro; Valentina Berto; Beatrice Gaia Aleandri; Francesco Folino; Stefania Barozzi; Diego Zanetti; Paola Marchisio (Brain Sciences)
Background/Objectives: Recurrent acute otitis media (rAOM) is a common disease in childhood, but its impact on the vestibular system remains poorly understood. The present study aimed to evaluate the long-term effects of rAOM on balance and vestibular function in pediatric patients. Methods: A total of 55 children, aged 8 years (25 males and 30 females), with a documented history of rAOM, no AOM episodes in the past year, and no previous ear surgery were assessed. Static posturography was used to assess postural instability, measuring sway area (SX, mm2) under four conditions: eyes open and eyes closed, with and without foam pads. Vestibular function was evaluated using the video head impulse test (v-HIT) to quantify vestibulo–ocular reflex (VOR) gain and corrective saccades across all six semicircular canals. Results: Children with a history of rAOM demonstrated significantly greater postural instability than healthy controls (p < 0.001 for all test conditions). The number of AOM episodes was the primary factor influencing balance dysfunction, with children who had more than eight episodes showing the most pronounced deficits in postural stability (p < 0.05). In some cases, the v-HIT revealed hypofunction in the right anterior (14.5%), left posterior (7.3%), left lateral (5.5%), left anterior (3.6%), and right posterior (3.6%) semicircular canals. Conclusions: The results of this study suggest that rAOM can lead to lasting balance and vestibular dysfunction, highlighting the importance of early monitoring and potential rehabilitation.